Semantics Analysis on the Relation of Meaning of Cultural Differences toward the Translation from Bahasa Indonesia to English - Danti Pudjianti (Buletin Al-Turas, 2010)
This article aims to explain how to translate the words of Bahasa Indonesia with the local cultural meaning, as sources language, to English, as target language. the mentioned words are taken from short story and would translate in the level og textual and referential level. firstly, it tried to find the meaning of the words based on the bilingual dictionary, Indonesian-English. Furthermore, they are consulted to the monolingual dictionary. finally the translation used is those accepted in target language speaking through the translation techniques, namely contextual conditioning.